#### Answer

(-3,2)

#### Work Step by Step

For this problem,
Equation 1: x - 4y = -11
Equation 2: x + 3y = 3
For substitution we need to solve for a variable. In this problem, we will solve for x in Equation 2 to get Equation 3:
x = 3 - 3y (Equation 3)
We then substitute that into Equation 1 and solve for y:
(3 - 3y) - 4y = -11
3 - 7y = -11
-7y = -14
y = 2
We then use Equation 3:
x = 3 - 3(2)
x = 3 - 6
x = -3
Therefore (-3,2) is a solution. Furthermore, the two graphs cross at (-3,2), so the answer is confirmed.